The use of rhythmic activities to improve gait parameters in ataxic patients: a case study (Revista Brasileira Multidisciplinar, 2024)
The term ataxia means “disorder”, describing the lack of organization of movements. Inaddition, the dysfunction causes changes in the speed, amplitude and strength of movements,with deficits in motor coordination, balance, and consequent gait disturbance, which makesdaily activities difficult. This work is a case study with the aim of analyzing the effects ofrhythmic activities on gait parameters, quality of life and reduction of falls in ataxic patients,through sound stimuli. F.V.L., 55 years old, male, participated in 10 physical therapy sessions,twice a week for 60 minutes. For the evaluations, the Time Up and Go test, the SF-36 Qualityof Life Questionnaire and gait assessment were used, which were carried out in two moments,before the intervention and at the end of the study. The therapy consisted of preparatoryactivities with the aim of stimulating body stability and functional activities, which wereperformed with the aid of a metronome that dictated the rhythm of the function. As a result,there was an improvement in gait parameters, such as stride and step length, step width andspeed. Therefore, it is concluded that the use of sound stimuli by the metronome can positivelyinfluence the gait of the ataxic patient.
Keywords: ataxia; walking pace; auditory stimulation